The combination of mental and cognitive maps strategies influenced the performance and accuracy of overwhelming volleyball skill - حنان طاهر حسن أ.د إنتصار عويد علي (الرياضة المعاصرة)
The study seeks to prepare an educational curriculum by employing the mixing strategies of mental and knowledge maps and learning about its effect on learning the performance of the skill of overwhelming hitting with volleyball and its accuracy among fifth-graders students. The two researchers assumptions the experimental approach by designing the experimental groups and controlling (51) students who were deliberately selected at a rate of (55.914%) from Al-Mustansiriya prep in Salah Uddin Governorate for the academic year (2019-2020). The approved scores were the skill performance tests for the overwhelming multiplication skill and accuracy after being photographed before and after and evaluated, as they applied the learners in the experimental group by (4) educational units according to the weekly lessons schedule, they were devoted(3) groups for learning the performance and (1) to learn the accuracy as it was employed The concepts of mixing the two strategies in (2 x 3) flexes are presented with the application of educational exercises to activate the role of learners in the lesson and according to the specifics and steps mentioned. After completing the experiment according to the mentioned experimental design determinants, the researcher has verified the results with the Social Statistical Bag System (SPSS-V26) To be the first You will conclude and applications that the application of mixing strategies of mental and cognitive maps helps in improving the learning of the performance of the overwhelming beating skill of the plane and its accuracy among the fifth preparatory students, and excels at improving learning of its performance and accuracy among students who are educated in the methods used in the lesson of physical education, and attention must be taken to adopting practical applications to mix the teaching strategies That is concerned with the cognitive structure and further strengthening the link between the performance experiences of the skill of overwhelming and accurate information in the main section of the physical education lesson, and it is necessary to pay attention to the availability of differentiated flex C mental and cognitive mapping strategies in volleyball halls in middle schools.